Press, Graphic Humor and Feminisms in Argentina: a trajectory with Mara Burkart (TEL Tempo, Espaço e Linguagem, 2024)
Linked to the dossier “Feminist Paths: reflections, potentialities and transformations of contemporary thinkers", we close this issue of TEL Magazine with an interview with professor Dr. Mara Burkart, one of the most important humor researchers in Argentina.